(untitled) (Trabalho & Educação, 2016)
In recent years, most workers were confronted with the obligation to work over about more ten years than expected as a result of the extension of the retirement age. Also, teachers are covered by this new situation. Given some specifics of the teaching profession, either as to the nature of the activity carried out, either on the diversity of situations including (for example, education sectors), in the study that supports this article, it was intended to produce preliminary data on the prospect of teachers on aging in general and its aging in the exercise of the teaching profession. In the exploratory study, there were collected biographical narratives of two portuguese teachers, a higher education and other pre-school education. The narratives revealed that there is a profound relationship of the aging process with key dimensions of the teaching profession in general and to specific levels of education. The passion for teaching was present in the narratives, as well as the disenchantment caused by working conditions and current educational policies in Portugal, which made evident with the need for policy decision-making to improve this situation. Also seen as necessary, was the question of better preparation of teachers / as for the subsequent phase to the active professionals. ___ Nos últimos anos, a maioria dos trabalhadores foi confrontada com a obrigação de trabalhar mais cerca de dez anos do que previsto, em consequência da extensão da idade da reforma. Também os professores são abrangidos por esta nova situação. Dadas algumas especificidades da profissão docente, quer quanto à natureza da atividade realizada, quer quanto à diversidade de situações que inclui (por exemplo, os setores de ensino), no estudo que sustenta este artigo, pretendeu-se produzir dados preliminares relativamente à perspectiva de professores sobre o envelhecimento em geral e o seu envelhecimento no exercício da profissão docente. No estudo exploratório recolheram-se narrativas biográficas de duas professoras portuguesas, uma do ensino superior e outra do ensino pré-escolar. As narrativas nos revelaram que há uma profunda relação do processo de envelhecimento com dimensões centrais da profissionalidade docente em geral e específicas aos níveis de ensino. A paixão pelo trabalho docente esteve presente nas narrativas, assim como o desencanto causado pelas condições de trabalho e políticas educativas atuais em Portugal, o que tornou evidente a necessidade de tomadas de decisão políticas para melhorar este quadro. Igualmente necessária, revelou-se a questão de se pensar melhor a preparação dos professores/as para a fase posterior ao exercício profissional efetivo.